ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PETANI APEL DI KABUPATEN MALANG - Andri Ashari; Aris Soelistyo; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2019)
Bengkaras Sub-Village, Madiredo Village, Pujon District is chosen as the research site because it is one of the central productions of apple in Malang Regency. This research aims to (1) calculate the income of apple farmers in Bengkaras Sub-Village, Madiredo Village, Pujon District, Malang Regency, (2) find out the factors affecting the income of the apple farmers in Bengkaras Sub-Village, Madiredo Village, Pujon District, Malang Regency.The research area is determinded based on purposive method. This research uses descriptive methode with qualitative approach. Sensus method was conducted by taking the whole population of 48 people as a sample. The characteristic of the sample is farmers who have 1 hectare of field. The data type used in this research are primary and secondary data.The result of this research shows that (1) fertilizer cost have positive effect towards the income of apple farmers, (2) size of the plantation area have positive effect towards the income of apple farmers, (3) total manpower have positive effect towards the income of apple farmers